Induced electric field intensification of acid hydrolysis of polysaccharides: Roles of thermal and non-thermal effects. (April 2020) - Li, Dan-Dan; Yang, Na; Tao, Yang; Xu, En-Bo; Jin, Zheng-Yu; Han, Yong-Bin; Xu, Xue-Ming
Abstract: The mechanism of induced electric field (IEF)-assisted acid hydrolysis was investigated by using guar gum, chitosan, and pectin as model polysaccharides. Roles of thermal and non-thermal effects were explored by temperature determination, HPSEC-MALLS-RI, SEM, FT-IR, XRD, and a rheometer. Results suggested that IEF affected the hydrolysis of polysaccharides by inducing thermal and non-thermal effects. Thermal effect contributed to the hydrolysis. As the excitation voltage increased, the thermal effect enhanced, with a temperature increased by about 25 °C after IEF (75 V) treatment for 4 h. Non-thermal effect, induced by the rapid and directional migration of charged species, varied with the electrical properties of the polysaccharides. It enhanced the hydrolysis of guar gum and pectin but negatively impacted the chitosan due to their different migration directions under IEF. IEF-assisted hydrolysis damaged the structural compactness of polysaccharides and significantly decreased the viscosity of their solutions. This study clarified the hydrolysis mechanism of polysaccharides under IEF, providing a theoretical guide for the application of IEF in the chemical modification of biopolymers. Graphical abstract: Image 1 Highlights: IEF affected the hydrolysis of polysaccharides by thermal and non-thermal effects. Thermal effect enhanced with increasing excitation voltage. Non-thermal effect varied with the electrical properties of polysaccharides. IEF-assisted hydrolysis damaged the structural compactness of polysaccharides. IEF-assisted hydrolysis significantly decreased the viscosity of polysaccharides.